2013
DOI: 10.1542/peds.2012-3774
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Use and Polypharmacy in Children With Autism Spectrum Disorders

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Psychotropic use is common and increasing in children with mental disorders but little is known about the long-term patterns of psychotropic use and polypharmacy among commercially insured children with autism spectrum disorders. WHAT THIS STUDY ADDS:Among 33 565 children with autism spectrum disorders, 64% used psychotropic medications and 35% had evidence of polypharmacy. Older children and those who had seizures, attention-deficit disorders, anxiety, bipolar disorder, or depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
140
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 21 publications
(19 reference statements)
11
140
4
2
Order By: Relevance
“…In the first study, no association was observed between polypharmacy and poverty level, parent education or marital status (Memari et al, 2013). In the second study, household income, overall, was also mostly unrelated to polypharmacy (Spencer et al, 2013), but, no studies have considered the impact of other parent factors on psychotropic polypharmacy.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In the first study, no association was observed between polypharmacy and poverty level, parent education or marital status (Memari et al, 2013). In the second study, household income, overall, was also mostly unrelated to polypharmacy (Spencer et al, 2013), but, no studies have considered the impact of other parent factors on psychotropic polypharmacy.…”
mentioning
confidence: 92%
“…Only four studies of children with ASD (Coury et al 2012, Logan et al 2012, Memari et al 2012, Spencer et al 2013) have examined factors associated with psychotropic polypharmacy, which have primarily focused on child demographic and clinical characteristics. Results of a large US study of 2,853 children and adolescents with ASD identified that greater age, Caucasian race, and nonHispanic/Latino ethnicity were associated with the use of multiple psychotropic medications (Coury et al 2012), along with gastrointestinal and sleep problems.…”
mentioning
confidence: 99%
See 3 more Smart Citations